Isotretinoin and inflammatory bowel disease - Rolanda, Carla (2007)
[Excerpt] We read with great interest the recent review published in your Journal by Reddy et al., which suggests a possible association between isotretinoin use and inflammatory bowel disease (IBD) (1). Although IBD is described as a possible adverse drug reaction in the product information, little attention has been given in the literature to this association.[...]